Gestión pedagógica en el aula: “Clima social escolar, desde la percepción de estudiantes y profesores del séptimo año de educación básica de los centros educativos Unidad Educativa La Salle de la ciudad de Quito, cantón DM Quito y escuela fiscal mixta Rumiñahui de la ciudad de Sangolqui, cantón Rumiñahui, provincia Pichincha, 2012-2013 - Calahorrano Teran, Jerson Gerardo (2013)
The pedagogical activity in Education is an important aspect to be considered in the class, so new methods and techniques must be generated in order to develop good quality interpersonal relationships, in order to get THE GOOD LIVING STATUS. This research goal is to analyze the pedagogical activity, the rules respect and the social atmosphere in the classroom as learning generators. The research was developed at Unidad Educativa “La Salle” located in Quito and at Rumiñahui coeducading public school placed in Sangolqui city, Rumiñahui canton. Researching methods used were: descriptive, analytic, synthetic, statistic and historical methods; researching techniques the bibliographic and at place; the instruments applied were Moos and Trickett’s CES which auto-evaluate Teacher’s learning activity, evaluation made by the student’s, observation charts used by teachers. It is considered relevant to pay attention to individual differences, the needs of students and evaluation criteria will permit us to get a better quality of education. I invite the reader to share the following proposal handled by the author.